2008
DOI: 10.1074/jbc.m800656200
|View full text |Cite
|
Sign up to set email alerts
|

CKIα Is Associated with and Phosphorylates Star-PAP and Is Also Required for Expression of Select Star-PAP Target Messenger RNAs

Abstract: We have recently identified Star-PAP, a nuclear poly(A) polymerase that associates with phosphatidylinositol-4-phosphate 5-kinase I␣ (PIPKI␣) and is required for the expression of a specific subset of mRNAs. Star-PAP activity is directly modulated by the PIPKI␣ product phosphatidylinositol 4,5-bisphosphate (PI-4,5-P 2 ), linking nuclear phosphoinositide signaling to gene expression. Here, we show that PI-4,5-P 2 -dependent protein kinase activity is also a part of the Star-PAP protein complex. We identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 26 publications
5
89
0
Order By: Relevance
“…The authors suggested that antioxidant response induces the assembly of the Star-PAP complex, leading to a rapid initiation of 3 0 -end formation and polyadenylation by the Star-PAP complex. Moreover, the PI4,5P 2 sensitive kinase CKIa is important for the production of the Star-PAP target mRNAs, including HO-1, however, in contrast to PIPKIa, CKIa is not necessary for HO-1 induction but only for basal expression [5]. Whether there is any link between Star-PAP complex and Nrf2 transcription factor is not known yet, although the involvement of STAR-PAP in tBHQ-induced expression of HO-1 suggests such an interaction, as tBHQ is a potent activator of Nrf2.…”
Section: Regulation Of Heme Oxygenase-1 Expressionmentioning
confidence: 93%
“…The authors suggested that antioxidant response induces the assembly of the Star-PAP complex, leading to a rapid initiation of 3 0 -end formation and polyadenylation by the Star-PAP complex. Moreover, the PI4,5P 2 sensitive kinase CKIa is important for the production of the Star-PAP target mRNAs, including HO-1, however, in contrast to PIPKIa, CKIa is not necessary for HO-1 induction but only for basal expression [5]. Whether there is any link between Star-PAP complex and Nrf2 transcription factor is not known yet, although the involvement of STAR-PAP in tBHQ-induced expression of HO-1 suggests such an interaction, as tBHQ is a potent activator of Nrf2.…”
Section: Regulation Of Heme Oxygenase-1 Expressionmentioning
confidence: 93%
“…However, in a proteomic study of the mRNA polyadenylation complex, only its close relative PAPg was recovered (Shi et al 2009). In addition, it has recently transpired that a subset of mRNAs are polyadenylated by the more distantly related poly(A) polymerase called Star-PAP/PAPD2 in response to specific signal transduction (Gonzales et al 2008). Strikingly, 80% knockdown of PAPa only has a small effect on the poly(A) population in the cell, but still causes a significant reduction in the induction of CXCL1, CCL2, and IL8 mRNA, suggesting that PAPa is perhaps more important for the expression of inflammatory genes than for general gene expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nuclear PI4,5P 2 also functions as a direct messenger that binds and regulates nuclear PI4,5P 2 effectors. Recent progress has identified a set of nuclear PI4,5P 2 effectors directly involved in multiple processes, including transcription [177180], mRNA processing [181185], mRNA export [186, 187], chromatin remodeling [180], stress responses [185], DNA repair, and mitosis [188]. The PIP kinases responsible for PI4,5P 2 generation in the nuclear envelope are not clear, but the intra-nuclear PIP kinases and PI4,5P 2 signaling are more defined.…”
Section: Pip Kinases Regulate Pi45p2 Effectors In the Nucleusmentioning
confidence: 99%
“…The PI4,5P 2 generated by PIPKIα appears to directly activate Star-PAP and also regulates other components of the Star-PAP complex, as exemplified by the Ser/Thr kinase casein kinase I (CKI) and protein kinase C δ (PKC5), both of which are required to activate Star-PAP for mRNA processing [181, 182, 185]. The functionally redundant CKI isoforms α and ε phosphorylate Star-PAP at the proline rich region (PRR) upon oxidative stress, which is critical for Star-PAP polyadenylation activity.…”
Section: Pip Kinases Regulate Pi45p2 Effectors In the Nucleusmentioning
confidence: 99%